Quality Control Applications - Chorafas, Dimitris N. (Springer Series in Reliability Engineering,, 2013)
Quality control is a constant priority in electrical, mechanical, aeronautical, and nuclear engineering – as well as in the vast domain of electronics, from home appliances to computers and telecommunications. Quality Control Applications provides guidance and valuable insight into quality control policies; their methods, their implementation, constant observation and associated technical audits. What has previously been a mostly mathematical topic is translated here for engineers concerned with the practical implementation of quality control. Once the fundamentals of quality control are established, Quality Control Applications goes on to develop this knowledge and explain how to apply it in the most effective way. Techniques are described and supported using relevant, real-life, case studies to provide detail and clarity for those without a mathematical background. Among the many practical examples, two case studies dramatize the importance of quality assurance: A shot-by-shot analysis of the errors made in the Fukushima Daiichi nuclear disaster; and the engineering failure with new technology due to the absence of quality control in an alternative energy project. This clear and comprehensive approach makes Quality Control Applications an essential reference for those studying engineering as well industry professionals involved in quality control across product and system design.